(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A Study To Evaluate The Effectiveness Of Human Patient Simulation On Knowledge And Practice Of Selected Procedures Among 3rd Year Bsc (N) Students In Selected Nursing Colleges At Rajkot , Gujarat.